2017
DOI: 10.1111/1753-6405.12667
|View full text |Cite
|
Sign up to set email alerts
|

Do childcare menus meet nutrition guidelines? Quantity, variety and quality of food provided in New Zealand Early Childhood Education services

Abstract: Objective: To describe food provision and evaluate menus in New Zealand childcare services, determining associations with service characteristics and/or cost of menu.Methods: Licensed services in three regions of New Zealand participated in an online survey, uploading a weekly menu where applicable. Menus were scored for compliance with guidelines on quantity, variety and quality of foods served. Bivariate and multivariate associations between menu score and service characteristics were analysed.Results: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…It is also recommended by INFORMAS to include early child care and/or education settings. These settings have been studied previously in NZ and were therefore not included as part of this national study and the resulting country profile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also recommended by INFORMAS to include early child care and/or education settings. These settings have been studied previously in NZ and were therefore not included as part of this national study and the resulting country profile.…”
Section: Methodsmentioning
confidence: 99%
“…These settings have been studied previously in NZ [40][41][42] and were therefore not included as part of this national study and the resulting country profile.…”
Section: Methodsmentioning
confidence: 99%
“…Esta situación evidencia la urgencia de políticas y lineamientos que promuevan donaciones bajo un patrón de alimentación saludable para los niños(as). Dada la posición estratégica de este tipo de ONG, es vital regular tanto los tamaños de porción como el tipo de alimentos ofrecidos con el fin de contribuir a replicar hábitos de alimentación adecuados como estilo de vida 16 .…”
Section: Variable Preescolar Escolarunclassified
“…Despite the existence of setting-specific dietary guidelines, previous national and international research has identified that such recommendations are poorly implemented. For example, a 2017 study assessing 57 childcare service menus in New Zealand reported only 5% of menus met criteria relating to quality, variety and quality of foods [ 12 ]. In Australia, a 2017 audit of 70 menus from childcare services across New South Wales (NSW) determined that none of the menus were compliant with nutrition guidelines [ 13 ].…”
Section: Introductionmentioning
confidence: 99%